Value Perceptions and Halal Label Usage: The Roles of Relogion and Culture in Shaping Purchase Intentions Toward Food Production in Sukabumi City - Nuryusuf, Mawaddah Haruman; Trapsila, Aji Purba (Islamic Economics and finance in Focus, 2025)
This study aims to identify the impact of perceived value and perceived usefulness on the intention to purchase halal-labeled food products, as well as how cultural and religious factors influence the purchase intention of halal-labeled food products among Muslim residents in Sukabumi City. The study employs a quantitative approach using the cluster sampling method, in which the Muslim population in Sukabumi City is divided into seven sub-districts as regional clusters. A total of 275 respondents were selected and measured using a structured questionnaire. Data analysis was conducted using Structural Equation Modeling (SEM) to examine the relationships among latent variables. The findings indicate that perceived value and perceived usefulness have a significant influence on purchase intention, while cultural collectivism and individualism show varying contributions depending on their vertical and horizontal dimensions. Religiosity was found to play an important role as a moderating variable, either strengthening or weakening the influence of culture and perceptions on purchase intention. This study provides valuable insights into the interaction between individual values, social norms, and religious beliefs in shaping halal consumption decisions.